Pergeseran Orientasi Kerja Pemuda di Desa Patannyamang, Kecamatan Camba, Kabupaten Maros - Maulana Ahsan; Rahmat Muhammad; Sakaria Anwar (Hasanuddin Journal of Sociology, 2021)
This study aims to determine the shift in youth work orientation in Patannyamang Village, Camba District, Maros Regency. In reviewing this research using the theory of social change. This research uses quantitative research method with descriptive type. The basis of the research used is a survey and the technique of determining the sample using simple random sampling with the technique of calculating the sample using the slovin formula. The results of this study illustrate that the majority of youth no longer have a work orientation as farmers and are more oriented towards work in the non-agricultural sector. There was a shift in work orientation among the youth of Patannyamang Village from the agricultural sector to the non-agricultural sector. Village youth view farming as unattractive and less promising. Meanwhile, non-agricultural sector jobs are seen as more promising and more comfortable to do. Keywords: Social change, Shift, work orientation, majority, youth